Garden anywhere : how to grow gorgeous container gardens, herb gardens, kitchen gardens, and more, without spending a fortune - Fowler, Alys. (San Francisco : Chronicle Books, 2009)
A guide to gardening in small spaces, covering container gardens, herb gardens, and kitchen gardens; with information on soil, compost, pruning, harvesting, tools, and resources; and focusing on organic methods.
From the ground up -- No-garden gardening -- How does your garden grow? -- Sowing, growing & protecting -- Pruning & propagating -- Defending your bounty -- The harvest -- Under the radar -- The directory.
"First published in Great Britain in 2008 by Kyle Cathie Ltd."--T.p. verso.
Includes index.
Keywords: Container gardening; Herb gardening; Patio gardening; Gardening